Transforming Engineering Education Exploiting Inveterate Symbiosis between Science and Spirituality - Jha, S. K. (Journal of Engineering Education Transformations, 2015)
The main objective of the present paper is to investigate and exploit the inveterate symbiosis between science and spirituality. From the stand point of human system being most complex in the world and creator of all the system, need to be more conscientious and scrupulous in order to develop advanced form of civilization. In view of contagious and ubiquitous terrorism, barbarity and savagery, its ischolar_main causes and remedy has been tried to be found out. Analogy between man and machine has been taken to understand the scope of rapprochement between bestial instinct and humane instinct. These tasks has been accomplished by taking inference of different control approaches such as transfer function approach, pole placement approach and above all robust and optimal control approaches. True implication of success and failure is analogically portrayed by the example of DC machine. Psychic control of human being vis-Ã -vis the stability of control systems with reference to the left half and right half s-plane poles and zeros has been analogically and symbiotically highlighted and presented.